Smart city ambulance for tracking shortest path using global position system - M.Prakash, Dr; Nithyanantham, S.; Nishanth, V; Prakash, A; Kaviyarrasu, D (International Journal of Engineering and Technology, 2017)
Traffic overcrowding and tidal flow management were identified as major problems in modern urban areas, which have caused much uncomfortable for the ambulance. Moreover, road accidents in the city have been nonstop and to bar the loss of life due to the accidents is even more crucial. To implement this, we introduce a scheme called Smart city ambulance system using shortest path finding algorithm and traffic signals. The main theme behind this scheme is to provide a smooth flow for the ambulance to reach the hospitals in time and thus minifying the expiration. The ambulance driver will send the request to control room. After receiving the request from control room then the ambulance is controlled by the control room which furnishes the most scant route to the ambulance and also controls the traffic light according to the ambulance location and thus reaching the hospital safely. The control room will send the alert message to the hospital. This scheme is fully controlled by control room, thus it controls the traffic lights, helping to reach the hospital in time using the shortest path Dijkstra algorithm